2017
DOI: 10.3386/w23963
|View full text |Cite
|
Sign up to set email alerts
|

The Lifetime Costs of Bad Health

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 2 publications
4
16
0
Order By: Relevance
“…We found relatively little evidence against the assumption of a single health index in our reduced form analysis, and this finding supports the use of a single index in structural models. In fact, the vast majority of life cycle models that account for health consider only a single health index (see French, 2005;French and Jones, 2011;French et al, 2018;Braun et al, 2015;De Nardi et al, 2017;Pashchenko and Porapakkarm, 2013;Aizawa and Fu, 2017, as well as the references in Footnote 24. Exceptions include Capatina et al, 2018, andGustman andSteinmeier, 2014).…”
Section: Using the Reduced Form Regressions To Assess Structural Models Of Healthmentioning
confidence: 99%
“…We found relatively little evidence against the assumption of a single health index in our reduced form analysis, and this finding supports the use of a single index in structural models. In fact, the vast majority of life cycle models that account for health consider only a single health index (see French, 2005;French and Jones, 2011;French et al, 2018;Braun et al, 2015;De Nardi et al, 2017;Pashchenko and Porapakkarm, 2013;Aizawa and Fu, 2017, as well as the references in Footnote 24. Exceptions include Capatina et al, 2018, andGustman andSteinmeier, 2014).…”
Section: Using the Reduced Form Regressions To Assess Structural Models Of Healthmentioning
confidence: 99%
“…Recently, Autor et al (2019) and Lee (2019) noted that households respond to a breadwinner's bad health event by adjusting the spousal labor supply, implying that the welfare consequences of bad health go beyond the individual. On an aggregate level, De Nardi et al (2018) document how poor health outcomes accumulate over the life cycle and shape economic inequality in the United States. Our analysis quantifies the interplay between the effects of occupation-level characteristics and poor health on the labor supply decisions of individuals.…”
Section: A Related Literaturementioning
confidence: 99%
“…This medical expenses source of risk cannot be isolated using an empirical strategy that involves regressing the change in consumption on the change in health. While separate regressions can be run with earnings and medical expenditures as dependent variables, and this has sometimes revealed that loss of earnings is the greatest health-related economic risk (Di Nardi et al, 2017) even in environments with little or no formal health insurance (Gertler and Gruber, 2002), this does not tell us anything specific about informal insurance of medical expense specifically. 8 A metric that informs of exposure to medical expenditure risk exclusively is required.…”
Section: Consumption Smoothing Over Health Shocksmentioning
confidence: 99%
“…Only then will the cross-section distribution conditional on observable covariates be indicative of the distribution faced by any one household with those characteristics. This assumption is inconsistent with the dynamics of health and medical expenses, which are characterized by persistence and strong serial correlation arising from the chronic nature of many diseases (Feenberg and Skinner, 1994;French and Jones, 2004;Di Nardi et al, 2017). Calculation of a risk premium also requires making assumptions about preferences.…”
Section: Catastrophic Paymentsmentioning
confidence: 99%